Safety of pirfenidone in patients with idiopathic pulmonary fibrosis: integrated analysis of cumulative data from 5 clinical trials. Issue 1 (12th January 2016) - Lancaster, Lisa; Albera, Carlo; Bradford, Williamson Z; Costabel, Ulrich; du Bois, Roland M; Fagan, Elizabeth A; Fishman, Robert S; Glaspole, Ian; Glassberg, Marilyn K; King, Talmadge E; Lederer, David J; Lin, Zhengning; et al.
Abstract : Background: Pirfenidone is an oral antifibrotic agent that has been shown to reduce the decline in lung function in patients with idiopathic pulmonary fibrosis (IPF). We performed an integrated analysis of safety data from five clinical trials evaluating pirfenidone in patients with IPF. Methods: All patients treated with pirfenidone in the three multinational Phase 3 studies (CAPACITY (studies 004 and 006), ASCEND (study 016)) and two ongoing open-label studies (study 002 and study 012 (RECAP)) were included in the analysis. Safety outcomes were assessed during the period from the first dose until 28 days after the last dose of study drug. Results: A total of 1299 patients were included in the analysis. The cumulative total exposure to pirfenidone was 3160 person exposure years (PEY). The median duration of exposure was 1.7 years (range 1 week to 9.9 years), and the mean (±SD) daily dose was 2053.8 (±484.9) mg. Gastrointestinal events (nausea (37.6%), diarrhoea (28.1%), dyspepsia (18.4%), vomiting (15.9%)) and rash (25.0%) were the most common adverse events; these were generally mild to moderate in severity and without significant clinical consequence. Elevations in alanine aminotransferase or aspartate aminotransferase greater than three times the upper limit of normal occurred in 40/1299 (3.1%) patients (adjusted incidence, 2.3 per 100 PEY). Elevations were generally transient and reversible with dose modification or discontinuation. Conclusions: A comprehensive analysis of safety outcomes in a large and well-defined cohort of 1299 patients with IPF who were followed prospectively for up to 9.9 years demonstrated that long-term treatment with pirfenidone is safe and generally well tolerated. Trial registration numbers: NCT00287716, NCT00287729, NCT00662038, NCT01366209 .